Islamic Educational Strategies In Family Parenting: Shaping a Generation With Strong Character - Tata Pramesti, Falaah; Jinan, Mutoharrun (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aims to explore the implementation of Islamic values in family parenting practices in Wonolopo Village, Karanganyar Regency. Amid the challenges posed by modern influences such as globalization and digital technology, understanding how families uphold traditional Islamic teachings in their parenting strategies is crucial. Employing a qualitative approach, data were collected through interviews and observations of families actively practicing Islamic parenting. The study seeks to identify the core Islamic values integrated into parenting and to examine the challenges families face in maintaining these values. Findings reveal that families prioritize moral education and religious practices as foundational elements of child development, yet struggle to mitigate the adverse effects of modern technology and social change. The study concludes that while Islamic values significantly influence parenting strategies, greater community support and educational initiatives are essential to strengthen these values in contemporary society. By highlighting the importance of Islamic teachings in shaping a generation with strong character, this research offers valuable insights for educators and families navigating the complexities of modern parenting.